Nuove esplorazioni verbovisive. Forme e applicazioni di scrittura visuale negli artefatti contemporanei - Ludovica Polo (Ocula)
The urgency of communication has characterized verbo-visuality since its origin, driving artists and designers in pursuit of a supra-linguistic system to overcome the written language. With the beginning of the 21st century and digitalization, verbo-visuality has indeed found fertile ground in the concepts of multimedia, design hybridism, and in the visual potential of digital typefaces. This essay aims to explore and highlight the contemporary directions of the word-image dualism, developed both through the use of analog tools - as for some forms of asemic writing - and, mostly, through the applications of new technologies - including e-poetry, variable fonts, and machine learning applied to typography.